Firm lifecycles - Kozeniauskas, Nicholas (2022)
The factors determining firm size and growth are central to understanding aggregate economic growth, and the design of firm-level government policies that aim to promote growth, and smooth business cycles. Motivated by this we study the relative importance of initial conditions versus post-entry shocks in etermining firm outcomes, and the relative size of capital and labor market friction that firms face. Using detailed Portuguese firm data and a simple model to aid interpretation, we find that initial conditions play an important role in determining firm outcomes, and that capital market frictions are larger than labor market frictions. (JEL: D24, E22,E23, E24, J23)